Exploitation of striped snakehead (Channa striata) in Sempor Reservoir, Central Java, Indonesia: A proposed conservation strategy (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Setyaningrum N, Lestari W, Krismono, Nuryanto A. 2022. Exploitation of striped snakehead (Channa striata) in Sempor Reservoir, Central Java, Indonesia: A proposed conservation strategy. Biodiversitas 23: 3584-3592. Striped snakehead (Channa striata) has important economic value in freshwater systems, including Sempor Reservoir in Indonesia, where increases in catch sizes have resulted in a declining population. In this study, we determined its population size based on abundance and distribution of length and assessed the rate of exploitation based on estimated growth and mortality rates to determine a conservation strategy in Sempor Reservoir. The study was undertaken from March to October 2020. The method used was a purposive random sampling survey. Fish samples were taken from five stations with different land uses. The estimated growth, mortality, and exploitation rates were analyzed by Pauly's model using FISAT II. Channa striata abundance data were analyzed using a Kruskal-Wallis test. The results showed that the highest abundance of C. striata at the KW station was almost three times higher than at the BK station. The average size of the gonads at first maturity was 277.4 mm in females and 284 mm in males. The estimated growth parameters indicated an asymptotic length (L?) of 409.5 mm. An exploitation rate of 0.74 was classified as overfishing. The proposed conservation strategy is to limit the number of catches by as much as 44% and prohibit the catching of individuals with a length of 230-349 mm. Kedungwringin Station was defined as a reference area with the largest abundance and complete size distribution, namely, the pre-reproduction, reproduction, and post-reproduction stages. Bangkong Station was defined as a spawning ground because there were many fish in the reproductive stage and Sempor River Station was the nursery ground with mostly juvenile fish. These two sites must be protected for sustainable striped snakehead populations in the river and reservoir.
Keywords: Lentic waters, population, preservation, river